2017
DOI: 10.1136/bmjopen-2016-014508
|View full text |Cite
|
Sign up to set email alerts
|

Trends in diagnostic patterns and mortality in emergency ambulance service patients in 2007−2014: a population-based cohort study from the North Denmark Region

Abstract: ObjectiveDemand for ambulances is growing. Nevertheless, knowledge is limited regarding diagnoses and outcomes in patients receiving emergency ambulances. This study aims to examine time trends in diagnoses and mortality among patients transported with emergency ambulance to hospital.DesignPopulation-based cohort study with linkage of Danish national registries.SettingThe North Denmark Region in 2007–2014.ParticipantsCohort of 148 757 patients transported to hospital by ambulance after calling emergency servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
3
32
1
Order By: Relevance
“…As in other studies, women more often than men contacted out-of-hours primary care, and a considerable part of calls to out-of-hours primary care concerned children [29][30][31][32]. Two Danish studies on EMS contacts reported similar percentages of calls made by women, but these studies found a slightly lower mean age than found in our study [33,34]. This difference is likely to be due to our stratification into groups (children and adults) and exclusion of patients aged 13-18 years.…”
Section: Comparison With Existing Literaturesupporting
confidence: 62%
“…As in other studies, women more often than men contacted out-of-hours primary care, and a considerable part of calls to out-of-hours primary care concerned children [29][30][31][32]. Two Danish studies on EMS contacts reported similar percentages of calls made by women, but these studies found a slightly lower mean age than found in our study [33,34]. This difference is likely to be due to our stratification into groups (children and adults) and exclusion of patients aged 13-18 years.…”
Section: Comparison With Existing Literaturesupporting
confidence: 62%
“…Women more often than men contacted OOH-PC, and a considerable part of calls to OOH-PC concerned children [29][30][31][32]. Two Danish studies on EMS contacts reported similar percentages of calls made by women, but these studies found a slightly lower mean age than found in our study [33,34]. This difference is likely to be due to our stratification into groups (children and adults) and exclusion of patients aged 13-18 years.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 68%
“…These studies did not investigate whether the patients arrived at hospital after calling EMS or OOH-PC. However, it has previously been shown that a large proportion of patients brought to hospital after ambulance transport by EMS receive a broad range of diagnoses including nonurgent and/or non-specific diagnoses [21,38,39] and that a substantial proportion of patients with serious conditions such as myocardial infarction or stroke initially contact primary care (both during daytime and OOH) [40][41][42][43][44]. This could indicate some overlap in patient populations.…”
Section: Comparison With Literaturementioning
confidence: 99%